Laparoscopic intrauterine insemination in superovulated Chios breed ewes - LYMBEROPOULOS (Α. ΛΥΜΠΕΡΟΠΟΥΛΟΣ), A.; KÜHHOLZER, B.; AMIRIDIS (Γ.Σ. ΑΜΟΙΡΙΔΗΣ), G. S.; CHRISTODOULOU (Β. ΧΡΙΣΤΟΔΟΥΛΟΥ), V.; VAINAS (Ε. ΒΑΪΝΑΣ), E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Superovulation was induced by i.m. administration of 8.8 mg o-FSH in 8 standard doses. Using only one trocar, 0.3 ml of diluted semen (300X106 spermatozoa) was deposited intraluminally, 24-28 hours after oestrus expression, with a 20GX75 mm needle without any fixation of the uterine horns. The duration of the procedure was approximately 5 min per animal. The oocytes-zygotes collection was carried out 18-24 hours after insemination by flushing of the oviducts. The percentage of the collected zygotes varied between donors from 44.44% to 100%. Fertilization was confirmed by the existence of two pronuclei in 121 out of 140 collected oocyteszygotes. Out of the 26 ewes, in 14,10 and 2 the percentage of fertilized oocytes were 100%, 80.55% and 44.44%, respectively. The results from this study are compared with those from other laparoscopic techniques, cervical insemination or natural mating of superovulated ewes. The feasibility for the application of this method in embryo transfer programmes and in intrauterine insemination with frozen ram semen, is also discussed.